Diseño de una mezcla asfáltica permeable optima con agregados minerales de la zona - Arévalo Mazón, Juan Enrique (2021)
This research aims to find out the optimal combination of mineral aggregates in the local area, which is suitable for maintaining a high volume of voids, that is, to achieve a high permeability rate in hot asphalt mixtures with the capability to rapidly evacuating rainwater. Thus, it avoids flooding in road systems. In order to develop this work, the aggregates came from the river mines of Chambo, Puela and La Moya and the open-pit mining of Guamote. These aggregates were evaluated in their natural state, except for the aggregates of Guamote, which were analyzed and used in a crushed form. All the stone material was subjected to different standardized tests in order to determine the properties of origin and consensus, and then the data collected was used to compare with foreign road regulations, thus defining whether these are suitable for implementation in the production of permeable asphalt. Once the aggregates that do not meet the necessary properties have been selected and discarded, it became possible to find the optimal percentage of material through a combined granulometric curve, being able to fit into the granulometric bands provided by foreign regulations used in the implementation of permeable asphalt. Then, the briquettes were designed, made and tested by the Marshall method, using AC-20 asphalt cement provided by COVIPAL - RIOBAMBA. Hence, the values and data were obtained from the asphalt sample. The final permeable asphalt mixture was subjected to tests that indicate its level of permeability, tests that helped to know the behavior of the mixture in the presence of water, and data such as runoff coefficients, time, and water filtration capacity. Finally, a comparative analysis was carried out between the permeable asphalt mix with standard or conventional asphalt mixes implemented in road networks in the country